Impact of Legislation on Antibiotic Use and Awareness of Beekeepers - Croppi, Sofia; Yu, Lina; Robinette, Chris S.; Hassler, Edgar E.; Newmark, Adam J.; Scott, Andrew; Cazier, Joseph; Song, Junxia; Formato, Giovanni (Journal of Apicultural Science, 2021)
Legislation plays a key role in regulating beekeeping practices and biosecurity measures, but different countries present conflicting legislative frameworks in terms of allowing antibiotic use. Currently the EU and the UK only permit antibiotics under the cascade principle, but while the UK considers the application in cases of European Foulbrood, the EU strongly discourages antibiotic use. In the US, antibiotics are registered for honeybees and their treatments are regularly authorised. This study relied on an international survey to assess the current use of antibiotics and general awareness among beekeepers, within the three legislative contexts. The results showed a similar use of antibiotics in all three geographical areas, regardless of the legislative context. General use and awareness indicated that the EU and US would likely benefit from national inspectors. Furthermore, even though beekeepers were somewhat aware of the various risks associated with improper antibiotic use, they would likely benefit from targeted training on the matter.